(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Bicycle-related trauma is a common cause of injury in pediatric population and involves varied presentation from simple bruise to life threatening visceral injuries. Although isolated scrotal injuries occurring after bicycle accidents is common but mostly under-reported due to various factors. Our study focuses on isolated scrotal injuries in a remote hilly region of J&K. The population is mostly catered to by our institution, GMC, Doda. Aims & Objectives: To assess the pattern, management, and outcomes of isolated scrotal trauma in pediatric population caused by bicycle accidents in a remote hilly region of J&K, India. Material & Methods: This study was performed over a period of 5 years from April 2020 to March 2025. Medical records were reviewed to extract demographic data, mechanism of injury, clinical findings, imaging, results, management and outcomes. Results:-Out of 94 bicycle-related related trauma cases, 18 (19.15%) involved isolated scrotal injury. The mean age was 13.8 years (Range = 8-18). Most injuries were due to straddling impacts (11/18, 61.11%) followed by handlebar collisions (38.89%) while navigating hilly uneven terrain. Scrotal hematomas(12/18, 66.67%) were most common injury followed by testicular contusion (4/18, 22.22%) and testicular rupture (2/18,11.11%). Dopler Ultrasonography was used in all cases. Four patients required surgical exploration including two unilateral orchidectomies. Conservative management was done in 77.78% of patients. Mean follow-up was done for 6 months and showed complete recovery in 72.23% (13/18) of patientswith no complications. One patient of orchidectomy developed wound site infection and required re-admission and secondary suturing after debridement. Four patients of scrotal hematoma were lost to follow-up after 2 months. Conclusion:-Isolated scrotal injury due to bicycle accidents is not rare and primarily affects young males especially teenagers. Prompt imaging and appropriate intervention are key to testicular preservation. Public health measures including safety education, adult supervision and use of protective gear are needed.